Electron Traps in GaAs Grown by Molecular Beam Epitaxy on On-axis (100) and Off-axis Substrates - Sarmiento, R.; Somintac, A.; Guiao, L.; Agra, F.; Salvador, A. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Deep level transient spectroscopy (DLTS) was used to characterize the electron traps present in the bulk GaAs grown by molecular beam epitaxy (MBE) on on-axis (100) and off-axis (4° towards the (111) A direction) substrates. Two electron traps were obtained for each sample having identical corresponding peak locations in the DLTS spectra. The layer grown on the on-axis substrate has electron traps with activation energies of EC–0.454 eV and EC–0.643 eV and capture cross-sections of 1.205 x 10-14 cm2 and 3.88 x 10-15 cm2, respectively. The layer grown on the off-axis substrate has traps with activation energies of EC–0.454 eV and EC–0.723 eV and capture cross-sections of 2.060 x 10-14 cm2 and 4.40 x 10-14 cm2. The electron traps are possibly the M4 (or EL3) and EL2 (or EB4) traps commonly found in GaAs layers. Due to the high trap concentrations obtained and to the non-uniform trap concentration profile, As desorption may be considerable during growth.